New environmental friendly corrosion inhibitor of mild steel in hydrochloric acid solution: Adsorption and thermal studies. Issue 1 (1st January 2020) - Salman, Taghried A.; Jawad, Qusay A.; Hussain, Mohammed A. M.; Al-Amiery, Ahmed A.; Shaker, Lina M.; Kadhum, Abdul Amir H.; Takriff, Mohd S.
Abstract: In the present investigation, coumarin derivative 4-((4-amino-5-thio-1, 2, 4-triazol-3-yl)methyl)coumarin (ATTC) have synthesized as novel ecofriendly corrosion inhibitor and evaluated the corrosive inhibitive properties on mild steel in 1 M hydrochloric acid solution through weight loss, electrochemical impedance spectroscopy (EIS) and Potentiodynamic (PD) polarization techniques. The corrosion analysis results show that ATTC inhibitive corrosion by mechanism of adsorption and display inhibition performance around 96% at the concentration of 0.5 mM. From the morphology analysis by means of scanning electron microscopy (SEM) techniques of the protective film on mild steel surface, it was confirmed that adsorption of ATTC molecules appears on the mild steel surface through chemi-sorption, that additional retard the corrosion rate. The stability of ATTC molecule was investigated in the gaseous state and it has thio and mercapto forms. Based on of density functions theory (DFT) results, thio possess higher stability state compared with mercapto. From the thermodynamic parameters, it was found that the conversion of thio form to mercapto form is spontaneous and endothermic.